Pemanfaatan Media Publikasi Dalam Membangun Citra Daya Mart - Sumartono Sumartono; Muhammad Fariz Pratama (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2020)
AbstractDaya Mart is a retailer that successfully launched a minimarketbased community economic empowerment program that is different from other minimarkets. The focus of this research is corporate communication with the aim of the research to find out the use of media publications in building Daya Mart image. This study uses a constructivist paradigm with a case study method. The number of informants was 5 people who were selected through a purposive technique. The results showed that Daya Mart used PR Writing by utilizing the media publications of online portals, social media, pamphlets, magazines, television and radio media. PR Writing by Daya Mart : (1) To educate the public through the concept of